Asymmetric synthesis of (R)-(-)-baclofen via asymmetric dihydroxylation - Thakur, V. V.; Paraskar, A. S.; Sudalai, A. (Indian Journal of Chemistry Section B-Organic Chemistry including Medicinal Chemistry, 2007)
A short and efficient asymmetric synthesis of (R)-(-)-baclofen, a selective GABA(B) agonist has been described with an overall yield of 14% and 85% ee. The Os-catalyzed Sharpless asymmetric dihydroxylation of alpha,beta-unsaturated olefin constitutes the key step in introducing stereogenic centers into the molecule.
Keywords: asymmetric dihydroxylation; baclofen; cyclic sulfate; gamma-aminobutyric acid; Parkinsons' disease

Efficient total synthesis of (-)-(3S,6R)-3,6-dihydroxy-10-methylundecanoic acid - Pandey, Satyendra Kumar; Kumar, Pradeep (European Journal of Organic Chemistry, 2007)
An efficient enantioselective synthesis of (-)-(3S,6R)-3,6-dihydroxy-10-methylundecanoic acid (1) from epichlorohydrin is described. The key steps include Jacobsen's HKR, Sharpless asymmetric dihydroxylation, regioselective opening of epoxide and cyclic sulfate. ((c) Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2007).
Keywords: cyclic sulfate; Dihydroxylation; Grignard reaction; hydroboration-oxidation; Jacobsen's hydrolytic kinetic resolution (HKR); regio selectivity